1984
DOI: 10.1126/science.6732895
|View full text |Cite
|
Sign up to set email alerts
|

Insect Prothoracicotropic Hormone: Evidence for Two Molecular Forms

Abstract: In an insect, the tobacco hornworm Manduca sexta, the cerebral neuropeptide prothoracicotropic hormone (PTTH), the primary effector of postembryonic development, exists as two molecular forms. These two PTTH's elicit characteristic in vitro dose responses of activation of prothoracic glands from different developmental stages, an indication that during development the glands change in their sensitivity to the neurohormones. Both PTTH's are active in a specific in situ bioassay. Since they may be released in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…The structural dissimilarity of the two hormones means that there are different receptors that mediate a similar cell response. Indeed, the prothoracicotropic glands of Manduca sexta were sensitive to the small and large prothoracicotropic hormones, as demonstrated by Bollenbacher et al [6].…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The structural dissimilarity of the two hormones means that there are different receptors that mediate a similar cell response. Indeed, the prothoracicotropic glands of Manduca sexta were sensitive to the small and large prothoracicotropic hormones, as demonstrated by Bollenbacher et al [6].…”
mentioning
confidence: 77%
“…The structural dissimilarity of the two hormones means that there are different receptors that mediate a similar cell response. Indeed, the prothoracicotropic glands of Manduca sexta were sensitive to the small and large prothoracicotropic hormones, as demonstrated by Bollenbacher et al [6].Although initial observations pointed to bombyxin as a prothoracicotropic hormone 171, its biological function in B. mori remained obscure [8, 91. Bombyxin titers in the hemolymph of postembryonic B. mori showed no correlation with ecdysone during molting [ 101.…”
mentioning
confidence: 99%
“…In Lepidoptera, prothoracicotropic hormones (PTTH) are synthesized by neurosecretory cells of the CNS and act on the PG, thereby initiating a transductory cascade, which results in the up-regulation of ecdysteroid synthesis from its precursor cholesterol (4). PTTH activity has been found in brain extracts of several insect species like the lepidoptera Bombyx mori (5) and Manduca sexta (6); however, we are only beginning to identify the components of the transductory cascade.…”
mentioning
confidence: 99%
“…The brain of S. cynthia ricini contains two different classes of molecules with prothoracicotropic activity, big PTTH (about 35 kDa) and small PTTH (about 4 kDa), 33) as in the case of the tobacco hornworm Manduca sexta. 37) Bioassay results indicated that the SBRP molecules are S. cynthia ricini small PTTH. On the other hand, the putative S. cynthia ricini big PTTH, which is homologous to B. mori PTTH, shows 200 to 1,000-fold higher prothoracicotropic activity than SBRP-A1 and -B1 on a molar basis.…”
Section: Samia Bombyxin-related Peptides (Sbrps)mentioning
confidence: 99%